3-Thiopheneboronic acid: an effective additive for regulation on electrode/electrolyte interphase of lithium metal battery with high-loading cathode. (1st August 2021) - Ren, Wenhao; Huang, Yun; Li, Saisai; Gan, Junyuan; Yang, Jun; Li, Xing; Wang, Mingshan; Cao, Haijun
Abstract: Lithium metal has been considered as a potential replacement for the commercialized graphite anode to further boost the energy density of Li-ion batteries. However, Li dendrite growth during Li plating/stripping causes safety concern and poor lifespan of Li metal batteries (LMBs). In addition, the deploy of Ni-rich high-loading LiNix Coy Mn1-x-y O2 (NCM, 0.6 ≤ x ≤ 0.95) is also an efficient way for boosting energy density. However, the dissolution of transition metal ion and structure evolution during cell operation can leave an adverse effect on cell performances. Herein, dual-functional 3-thiopheneboronic acid (TB) additive is used to form a lithium borate-rich solid electrolyte interphase (SEI) on Li anode and an improved cathode electrolyte interphase (CEI) on Ni-rich cathode. The TB-induced SEI layer is conductive and stable, and thus beneficial to improving kinetic limitation of Li nucleation and obtain a uniform morphology of Li deposition. When the TB-protected Li metal anode matches the high-loading LiNi0.6 Co0.2 Mn0.2 O2 (NMC622) cathode (13.65 mg cm −2 ), high initial capacities of 163.78 mAh g −1 (2.23 mAh cm −2 ) at 0.2 C and 164.82 mAh g −1 (2.25 mAh cm −2 ) at 0.5 C after activation are obtained, attributing to the effective SEI and stable CEI induced by TB. This strategy of introducing additives into LMB system with Ni-rich high-loading NMC cathode affords an emerging energy storage system to demonstrates the material engineering of batteries with very high energy density.